Generation of a new cancer model in zebrafish for studying apoptotic effects of anti-cancer drugs. - Peh, Yu Ming. (2013)
The murine melanoma B16-F10 cell line isolated from the C57Bli6 mice is a highly metastatic variant of the B16 cell line and has been a subject for studies for many years. Previously, caspase-3 activated FRET probe have been introduced into the cell to generate the B16-F10-C3 cell line that is capable of expressing a change in fluorescence emission when apoptosis is activated. In this project, B16-F10-C3 cells were injected into zebrafish embryo to generate a xenograft tumor model that is capable of expressing this particular sensor. Currently, even though many zebrafish models have been established for tumor growth, angiogenesis and drug screening, there is no record of caspase-3 sensor being adopted in these models. In the experiment, prior to in vivo drugs screening, the embryos and the cells were separately exposed to several anti cancer agents to examine the viability profile under exposure to different concentration. Subsequently, the injected embryos that undergo the drug treatments show signs of apoptosis or size reduction in the xenograft tumor which suggests that the viability and the proliferation of the cells were indeed suppressed. Hence, this model shows potentials in future drug screenings and provides promise for further research and usage.